1993
DOI: 10.1002/hep.1840180108
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and tissue levels of the neutrophil chemotaxin interleukin-8 are elevated in severe acute alcoholic hepatitis, and tissue levels correlate with neutrophil infiltration

Abstract: Acute alcoholic hepatitis is characterized by a unique degree of liver neutrophil infiltration, often accompanied by marked peripheral neutrophilia in the absence of demonstrable bacterial or fungal infection. In this study we assayed plasma and tissue levels of a potent neutrophil activator and chemotaxin, interleukin-8, in patients with a spectrum of alcoholic liver diseases and in normal and diseased control subjects. Levels of circulating interleukin-8 were undetectable in normal subjects but highly elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 27 publications
1
81
0
3
Order By: Relevance
“…[6][7][8][9][10][11] Experiments were performed using an in situ perfusion system of the rat femoral bone marrow. Thus, the chemokine rat MIP-2 was infused directly into the femoral bone marrow via the femoral artery, and mobilized leukocytes were collected via cannulation of the femoral vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] Experiments were performed using an in situ perfusion system of the rat femoral bone marrow. Thus, the chemokine rat MIP-2 was infused directly into the femoral bone marrow via the femoral artery, and mobilized leukocytes were collected via cannulation of the femoral vein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plasma levels of CXC chemokines rise during inflammatory reactions and contribute to the acute release of neutrophils from the bone marrow. [6][7][8][9][10][11] Therefore, to mimic an inflammatory reaction we have infused a pulse of the CXC chemokine, rat macrophage inflammatory protein-2 (MIP-2) to stimulate an acute mobilization of neutrophils from the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…Magnification: ϫ64 (a, d, and e), ϫ100 (c), and ϫ400 (b). as cirrhosis and alcoholic or autoimmune hepatitis, compared with those of normal controls (Sheron et al, 1993). In chronic hepatitis C, IL-8 -mRNA expression is also associated with a significant histological activity index (HAI) (Shimoda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…10 In certain pathological situations, IL-8 is produced excessively by a wide variety of cells and it is released in the circulation. Previous studies showed that IL-8 secretion or IL-8 gene expression in chronic or acute liver diseases such as cirrhosis and autoimmune or alcoholic hepatitis, were increased compared with normal controls, [13][14][15][16][17] but without attempts at defining which components of liver injury may be most affected.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Previous studies have shown that IL-8 secretion or IL-8 gene expression in chronic or acute liver disease, such as cirrhosis and alcoholic or autoimmune hepatitis, were increased compared with normal control groups. [13][14][15][16][17] However, the role of hIRH as well as IL-8 in the pathogenesis of hepatitis C virus (HCV)-related hepatitis remains unclear.…”
mentioning
confidence: 99%